2016
DOI: 10.1097/gox.0000000000000823
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Autologous Platelet-rich Plasma Glue in Weight Loss Sequelae Surgery and Breast Reduction: A Prospective Study

Abstract: Background:Seroma and hematoma formations are the most common complications after plastic surgery. The aim of this study was to assess the efficacy of autologous platelet-rich plasma (A-PRP) glue to reduce postoperative wound complications and improve surgical outcomes.Methods:Fifty-four patients were included in this study. They underwent breast reduction surgery, abdominoplasty, or limb lifting with A-PRP glue application on the entire surface of the subcutaneous tissue at the time of suture. Retrospective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…However, concerns have been raised regarding PRP use for regeneration or reconstruction on cancer tissue removal site because PRP contains and induces various growth factors and cytokines to promote cell proliferation and regeneration. There have been a few clinical studies reporting favorable outcomes of using PRP in breast reconstruction after mastectomy in breast cancer patients (43, 44). However, there is no study on endometrial PRP treatment after curettage in endometrial cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns have been raised regarding PRP use for regeneration or reconstruction on cancer tissue removal site because PRP contains and induces various growth factors and cytokines to promote cell proliferation and regeneration. There have been a few clinical studies reporting favorable outcomes of using PRP in breast reconstruction after mastectomy in breast cancer patients (43, 44). However, there is no study on endometrial PRP treatment after curettage in endometrial cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 case, PRP was applied to the donor site to accelerate wound healing [17]. Two studies aimed to reduce postoperative complications after breast reconstruction with PRP application [18, 19]. Another study investigated the effects of PRP injections in keloid scars with the objective to improve scar quality and reduce pain [20].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, Salgarello et al in a retrospective comparative study reported no superiority of the PRP-enriched fat grafting compared to the classic Coleman fat grafting alone in terms of clinical outcomes, rate of satisfaction and incidence of liponecrosis (28). Recently, however, Hersant et al revealed a lower incidence of hematoma formation in women undergoing breast reduction surgery with PRP-glue application compared to the control group but equivalent wound-healing quality (29).…”
Section: Post-mastectomy Breast Reconstruction: Platelet-rich Plasma mentioning
confidence: 99%